Domestic violence in Rawalpindi - Romana Malik, Romana Malik; Muhammad Hammad, Muhammad Hammad; Nasim Irshad, Nasim Irshad; Babur Rashid Chughtai, Babur Rashid Chughtai; Riffat Masood, Riffat Masood; Muhammad Asif Shahab, Muhammad Asif Shahab (Journal of Rawalpindi Medical College, 2020)
Objectives: To study the prevalence of domestic torture in Rawalpindi. Study design: Retrospective, cross-sectional. Place and duration of study: DHQ Hospital Rawalpindi, from 1st January 2016 to 31st Dec 2016. Material and methods: Record of Medico-legal cases of domestic violence was obtained from DHQ Hospital Rawalpindi. Analysis of all the domestic torture cases regarding age group involved, injury pattern, pregnant/non-pregnant victims, urban/rural distribution and culprits were done. Results: A total of 118 cases of domestic torture reported at the DHQ Hospital Rawalpindi. All the victims were females, 110 cases of blunt trauma and 8 cases of firearm injuries reported. 12 females were pregnant, the most common age group of victims was 20-30 years, and 113 cases belonged to urban areas as compared to only 5 cases of rural area. Conclusion: Effective legislation, strict implementation, awareness among public and speedy trial is required to control cases of violence in the society.